Phylogeography of the Maleo Senkawor (Macrocephalon maleo Sal. Muller 1846) Based on Cytochrome B Gene in Sulawesi And Their Sex Determination using Molecular Sexing - Abdul Samad; D D Solihin; Cece Sumantri; B Purwantara (Indonesian Center for Animal Research and Development (ICARD), 2023)
The Maleo Senkawor bird (Macrocephalon maleo) is endemic and widely distributed in Sulawesi. Maleo Senkawor bird is monomorphic so it is difficult to distinguish between male and female individuals. This study aimed to determine the kinship relationship among M. maleo in various geographic areas in Sulawesi through the use of the gene marker Cytochrome-b (Cyt-b), determine the sex ratio, and examine the reliability of the 2550F/2718R primer. Fifteen (feather and eggshell) samples from North Sulawesi, Southeast Sulawesi, and Central Sulawesi were collected. Total DNA isolation was performed using the Dneasy® Blood and Tissue kit (Cat. No. 69504) following a Qiagen protocol with modification. PCR amplification (35 cycles) used a forward primer MMCytb_F (5'- GAAAATCCCACCCCCTACTA-3'), a reverse primer MMCytb_R (5'- GTTGGCTACGAGGAGTCAGA-3') and a primer for sexing used 2550F/2718R. Analysis was performed on the length of 903 bp Cyt-b mtDNA gene sequences of M. maleo along with their amino acid sequences (301 AA) and Chromo Helicase DNA-Binding (CHD) gene sequences. Based on the genetic distance of the Kimura 2-Parameter model and p-distance, the interpopulation of M. maleo in Sulawesi (the population of Southeast Sulawesi was separated from the population of Central Sulawesi and North Sulawesi) was 0.002 (0.2%) – 0.003 (0.3%). Each population has formed a different haplotype. Primer 2550F/2718R was able to amplify the CHD gene and could distinguish the sex identification. Male individuals are more dominant than female individuals with a sex ratio of 6,5:1